Purwarupa Alat Pemilah Warna Barang Menggunakan Sensor TCS230 - Raharja, Wahyu Kusuma; Anindya, R.A. Sekar Ciptaning; Sari, M. Anggita; Saputra, J.F. (Jurnal Ilmiah Informatika Komputer, 2025)
Technological developments have driven automation in various industrial sectors, including color-based sorting systems. Currently, many industries still rely on human labor in the sorting process, which results in high operational costs and is prone to human error. This study aims to design a prototype of an object sorting device based on color using the TCS230 sensor integrated with an Arduino Uno and controlled by a PLC (Programmable Logic Controller) as the main unit. The system uses push buttons, TCS230 sensors, and proximity sensors as inputs, with the Arduino functioning as the initial signal processor. The PLC processes data sequentially to control the outputs, which include a DC motor as the conveyor drive, two pneumatic solenoids for item separation, and status indicator lights. Test results show that the TCS230 sensor consistently reads red (14.72 kHz), green (6.944 kHz), and blue (20.82 kHz) colors. The PLC responds according to logic as red activates solenoid 1, green activates solenoid 2, while blue does not trigger the actuator. The system has proven to be effective, accurate, and reliable, demonstrating significant potential for application in manufacturing, logistics, and recycling industries.